Experimental studies on characteristics of C.I engine by using fish oil as an alternative fuel. (2021) - Jacob, S.; Karikalan, L.
Abstract: The worldwide fuel crisis in year of 1970 has formed alertness between several countries of their weakness to the oil embargoes as well as shortage. Significant thought was alert on growth of an alternative fuel source such as diesel fuel and Blends of fish oil is investigated as well as establish to be technically possible. Therefore there is changed attention in the fish oil diesel blends by particular highlighting in the diesel engine. While taking into consideration AF is used in diesel engine. The principle of the paper is to evaluation this issue with specified reference to security as well as allocation. Performance features like brake thermal efficiency (BTC), specific fuel consumption (SFC), fuel power, and brake power of blended fuels were calculated and compared with gasoline fuel. These blends were namely B20, B30, B40, B50. The Performance parameters were quantified predicated on effective completion of engine standard tests carried out on a diesel engine tested a four stroke engine and variable speed C.I. Engine with eddy current dynameters. It can be culminated from the results that B30 & B40 are the most preferable blends for use in four stroke engine. The result is accomplished that the 8:3 percentage of the diesel as well as fish oil is most professional proportions.